2000
DOI: 10.1097/00000658-200007000-00008
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Pathway to Accelerate Recovery After Colonic Resection

Abstract: A multimodal rehabilitation program may significantly reduce the postoperative hospital stay in high-risk patients undergoing colonic resection. Such a program may also reduce postoperative ileus and cardiopulmonary complications. These results may have important implications for the care of patients after colonic surgery and in the future assessment of open versus laparoscopic colonic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
457
1
39

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 722 publications
(514 citation statements)
references
References 18 publications
17
457
1
39
Order By: Relevance
“…The ERP is a comprehensive perioperative CRS care pathway that has been shown to reduce postoperative morbidity and length of hospitalization. [9][10][11][12][13][14][15][16][17] Similarly, the SSIB is a perioperative care program that systematically provides evidence-supported measures for surgical wound infection prevention and has been shown to reduce the rate of postoperative wound infection. [18][19][20][21][22] Although both the ERP and SSIB have individually been shown to improve outcomes after CRS, the effect of their combined presence has not, to our knowledge, previously been reported in the literature.…”
mentioning
confidence: 99%
“…The ERP is a comprehensive perioperative CRS care pathway that has been shown to reduce postoperative morbidity and length of hospitalization. [9][10][11][12][13][14][15][16][17] Similarly, the SSIB is a perioperative care program that systematically provides evidence-supported measures for surgical wound infection prevention and has been shown to reduce the rate of postoperative wound infection. [18][19][20][21][22] Although both the ERP and SSIB have individually been shown to improve outcomes after CRS, the effect of their combined presence has not, to our knowledge, previously been reported in the literature.…”
mentioning
confidence: 99%
“…An obvious finding in the present study was that across the range of gastrointestinal cancer surgery a‐LOS was much longer than LOS reported in RCTs or single‐centre series4 5, 15. Seminal series have showed that open colectomy stays can be reduced to 2 days4, and laparoscopic surgery to just 23 h 5 .…”
Section: Discussionmentioning
confidence: 46%
“…Seminal series have showed that open colectomy stays can be reduced to 2 days4, and laparoscopic surgery to just 23 h 5 . Although these may have been intended as ‘proof of principle’, the present data showed a median a‐LOS of 8 days for open and 5 days for laparoscopic colonic resections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations